Шалый малый: [роман] / Екатерина Вильмонт ; [стихи Б. А. Абрамова] - Вильмонт Екатерина Николаевна (Астрель, 2012)
Экземпляры: ф.1 (2013) / Инвентарный номер: 49937 / Цена: / Сис.шифр: 84Р6 / Авт.знак: В 46 / ББК: 84(2Рос=Рус)6